A plant cell factor induces Agrobacterium tumefaciens vir gene expression - Stachel, Scott E. (1986)
The virulence genes of Agrobacterium are required for this organism to genetically transform plant cells. We show that vir gene expression is specifically induced by a small (<1000 Da) diffusible plant cell metabolite present in limiting quantities in the exudates of a variety of plant cell cultures. Active plant cell metabolism is required for the synthesis of the vir-inducing factor, and the presence of bacteria does not stimulate this production. vir-inducing factor is (i) heat and cold stable; (ii) pH stable, although vir induction with the factor is sensitive above pH 6.0; and (iii) partially hydrophobic. Induction of vir gene expression was assayed by monitoring β-galactosidase activity in Agrobacterium strains that carry gene fusions between each of the vir loci and the lacZ gene of Escherichia coli. vir-inducing factor (partially purified on a C-18 column) induces both the expression in Agrobacterium of six distinct loci and the production of T-DNA circular molecules, which are thought to be involved in the transformation process. vir-inducing factor potentially represents the signal that Agrobacterium recognizes in nature as a plant cell susceptible to transformation.